Object Recognization System - Juyal, Sidharth (Journal of Advanced Research in Signal Processing and Applications, 2023)
In recent years Artificial has shown immense growth and future scope. One specific area where its potential is growing with every passing year is Natural Language Processing (NLP).With the help of artificial intelligence voice assistants can communicate with users in natural language.They are very easy to use and today in this growing digital world their use is expected to grow only further. From being in our home speaker to in our pocket in the form of smartphones it is safe to say they have consolidated their position in our everyday life. The purpose of this research paper is to understand the growing use of voice assistants in our daily life.